A comprehensive review of the pyrolysis process: from carbon nanomaterial synthesis to waste treatment. Issue 1 (30th November 2021) - Devi, Mamta; Rawat, Sachin; Sharma, Swati
Abstract: Thermally induced chemical decomposition of organic materials in the absence of oxygen is defined as pyrolysis. This process has four major application areas: (i) production of carbon materials, (ii) fabrication of pre-patterned micro and nano carbon-based structures, (iii) fragmentation of complex organic molecules for analytical purposes and (iv) waste treatment. While the underlying process principles remain the same in all cases, the target products differ owing to the phase and composition of the organic precursor, heat-treatment temperature, influence of catalysts and the presence of post-pyrolysis steps during heat-treatment. Due to its fundamental nature, pyrolysis is often studied in the context of one particular application rather than as an independent operation. In this review article, an effort is made to understand each aspect of pyrolysis in a comprehensive fashion, ensuring that all state-of-the-art applications are approached from the core process parameters that influence the ensuing product. Representative publications from recent years for each application are reviewed and analyzed. Some classical scientific findings that laid the foundation of the modern-day carbon material production methods are also revisited. In addition, classification of pyrolysis, its history and nomenclature and the plausible integration of different application areas are discussed.